Combining Dark Energy Survey Science Verification data with near-infrared data from the ESO VISTA Hemisphere Survey. Issue 3 (28th November 2014) - Banerji, Manda; Jouvel, S.; Lin, H.; McMahon, R. G.; Lahav, O.; Castander, F. J.; Abdalla, F. B.; Bertin, E.; Bosman, S. E.; Carnero, A.; Kind, M. Carrasco; da Costa, L. N.; et al.
Abstract: We present the combination of optical data from the Science Verification phase of the Dark Energy Survey (DES) with near-infrared (NIR) data from the European Southern Observatory VISTA Hemisphere Survey (VHS). The deep optical detections from DES are used to extract fluxes and associated errors from the shallower VHS data. Joint seven-band ( grizYJK ) photometric catalogues are produced in a single 3 sq-deg dedicated camera field centred at 02h26m−04d36m where the availability of ancillary multiwavelength photometry and spectroscopy allows us to test the data quality. Dual photometry increases the number of DES galaxies with measured VHS fluxes by a factor of ∼4.5 relative to a simple catalogue level matching and results in a ∼1.5 mag increase in the 80 per cent completeness limit of the NIR data. Almost 70 per cent of DES sources have useful NIR flux measurements in this initial catalogue. Photometric redshifts are estimated for a subset of galaxies with spectroscopic redshifts and initial results, although currently limited by small number statistics, indicate that the VHS data can help reduce the photometric redshift scatter at both z  < 0.5 and z  > 1. We present example DES+VHS colour selection criteria for high-redshift luminous red galaxies (LRGs) at z ∼ 0.7 as well as luminous quasars. Using spectroscopic observations in this field we show that the additional VHS fluxes enable a cleaner selection of both populations with <10 per cent contamination from galactic stars in the case of spectroscopically confirmed quasars and <0.5 per cent contamination from galactic stars in the case of spectroscopically confirmed LRGs. The combined DES+VHS data set, which will eventually cover almost 5000 sq-deg, will therefore enable a range of new science and be ideally suited for target selection for future wide-field spectroscopic surveys.